Negative word of mouth and online shopping: Examining the role of psychological contract violation, trust and satisfaction - Sana Mehmood; Yasir Rashid; Salman Zaheer (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
In a highly competitive e-retailing world, service provision fulfilling the customer's expectations plays a crucial role in survival and sustainability of buyer-seller relationship. However, service failure could result in negative outcomes due to destruction of this relationship. From buyer-seller relationship perspective in online shopping context, the research regarding negative word of mouth (NWOM) resulting from psychological contract violation (PCV) is scarce and demands attention. Therefore, building on Stimulus-Organism-Response (S-O-R) model and PCV theory, this study examined the direct impact of PCV on NWOM through the mediating mechanism of trust and satisfaction. Data were collected using structured questionnaire and results were analyzed through structural equation modeling. The findings emphasized that PCV, due to unmet expectations of consumers in online shopping experience, positively influence NWOM directly and as well through satisfaction and trust. Both satisfaction and trust partially mediated the relationship between PCV and NWOM. These findings mainly contribute in the field of online retailing and suggest ways such as avoiding delivery delay of product, variation in quality of product, making it easy for customer to claim refund, non-delivery of product or out-of-stock items on online catalogs etc. Avoiding these can strengthen the buyer-seller relationship proactively via service provision in order to minimize the destructive negative outcomes.
Keywords: 330; psychological contract violation (PCV); negative word of mouth (NWOM); trust; satisfaction; stimulus-organism-response (S-O-R) model; online retailing